Automation of aquaponics systems through integration of RTC modules, turbidity sensors, and water level sensors - Jaya, Dicky Suman; Styawati, Styawati; Syahirul, Alim (Journal of Soft Computing Exploration, 2023)
Automation of aquaponics systems is key in increasing agricultural efficiency and productivity. A system considered an innovative method of sustainable food production that combines fish farming with agriculture simultaneously. The problem that often occurs is crop failure, due to the lack of technology that can monitor automatically, so that farmers experience losses as a result of fish and plant growth does not thrive, and problems in urban areas that require land for planting and fish farming due to limited land in urban areas. There is another problem with the lack of accurate timing and monitoring of water quality in aquaponics. The purpose of this research is to implement an IoT system in aquaponics that is connected to various sensors, such as Turbidity sensors, Water Level sensors, and RTC Modules. To monitor water quality conditions in tilapia habitat and accurate time measurement to provide fish feed automatically so as to improve fish health and growth and support better and consistent yields. The findings of this study show that the implementation of IoT systems in aquaponics can overcome environmental monitoring and control problems effectively. Using the integration of RTC modules, turbidity sensors, and water level sensors effectively improves the automation of aquaponics systems. This optimized system provides better monitoring of environmental conditions, reduces reliance on manual maintenance, and increases overall productivity. It helps increase tilapia growth and plant productivity in a modern aquaponics system. This research demonstrates the great potential of IoT technology in increasing efficiency and productivity in aquaponics aquaculture, so that it can push the fisheries sector towards a more advanced and competitive direction. So the main conclusion is expected that this automation can increase the productivity of ecosystem balance, and can face food security challenges and move towards more environmentally friendly solutions, towards effective management in the future.